Sixty years later: Emsland still without wildfowl? - Kruckenberg, Helmut (Wildfowl, 2021)
After the Second World War, G.L. Atkinson-Willes was stationed as an army officer in northwest Germany, where he studied waterbirds in the vicinity of Leer. On returning to the UK, he published a report about his observations at the Emsland (Atkinson-Willes 1961), having been deeply impressed not only by the birds but also by the scenery, and in his paper he made a call for the preservation of this threatened landscape and its avifauna. Sixty years later, weekly monitoring of waterbirds carried out in winters 2012/13–2019/20 provides an opportunity to verify whether his fears at that time were justified. In fact, during the second half of the 20th century the area largely lost its importance for wintering waterbirds, but when two flood polders were established in the late 1990s the area revived. Although not recapturing its pre-war significance, it is now once more of international importance for Greater White-fronted Geese Anser albifrons, Greylag Geese A. anser and Barnacle Geese Branta leucopsis, as well as for Bewick’s Swans Cygnus columbianus bewickii. For a further 13 species, including Ruff Philomachus pugnax, Great White Egret Egretta alba, Pink-footed Goose Anser brachyrhynchus and some duck species, the lowlands achieve national importance levels. Whilst the data in Atkinson-Willes’ publication were rather vague, it is evident that, although no longer the large-scale waterbird Eldorado of earlier times which he reported, nevertheless, the Emsland has regained importance for waterbirds during the last 20 years.